PSI-10 The Relationship Between Litter Size and Functional Teat Number at Farrowing on Litter Size at Weaning. (7th May 2021) - Speckman, Evan C; Howard, Jeremy T; Wiegert, Jeff G
Abstract: Sow functional teat number (FTEAT) is positively associated with piglet preweaning survival and litter throughput. The objective was to estimate the value of FTEAT in relationship to litter size to optimize the number of pigs weaned. Number of pigs born alive (NBA) and total teat number (TTEAT) were counted at farrowing on 836 multiparous purebred sows between March and September, 2020. Teats were evaluated by trained staff at farrowing and considered functional based on visual appraisal of teat morphology. Litter size at weaning (LSW) was recorded after a 26.5 d lactation length (LL). Sow was the experimental unit and all data were analyzed as a function of the biological sow. Number born alive was categorized by quartile: Q1 ≤ 10 NBA (n=185; µ=8.2); Q2 = 11 to 12 NBA (n=194; µ=11.6); Q3 = 13 to 14 NBA (n=238; µ=13.5); Q4 ≥ 15 NBA (n=219; µ=16.3). Data were analyzed in PROC GLM of SAS with farm, breed, and NBA quartile as categorical effects and LL and FTEAT as linear terms. The interaction of NBA quartile and FTEAT was also included. Mean TTEAT, FTEAT, LSW and preweaning survival were 15.4, 14.5, 11.3 and 89.4%, respectively. As a linear term, a one teat increase in FTEAT improved (P< 0.01) LSW by 0.3±0.1 pigs. Yet the value of an additional functional teat increased with increasing NBA. A one teat increase in FTEAT improved (P< 0.01) LSW in Q1, Q2, Q3, and Q4 by 0.12, 0.27, 0.33, and 0.38 pigs, respectively. The analysis demonstrates the impact of FTEAT on sow performance increases with increasing litter size, and highlights the importance of functional teats to optimize litter throughput and maximize the genetic potential of a maternal line.